Grey matter density changes of structures involved in Posttraumatic Stress Disorder (PTSD) after recovery following Eye Movement Desensitization and Reprocessing (EMDR) therapy. (30th August 2017) - Boukezzi, Sarah; El Khoury-Malhame, Myriam; Auzias, Guillaume; Reynaud, Emmanuelle; Rousseau, Pierre-François; Richard, Emmanuel; Zendjidjian, Xavier; Roques, Jacques; Castelli, Nathalie; Correard, Nadia; Guyon, Valérie; Gellato, Caroline; et al.
Abstract: Recovery of stress-induced structural alterations in Posttraumatic Stress Disorder (PTSD) remains largely unexplored. This study aimed to determine whether symptoms improvement is associated with grey matter (GM) density changes of brain structures involved in PTSD. Two groups of PTSD patients were involved in this study. The first group was treated with Eye Movement Desensitization and Reprocessing (EMDR) therapy and recovered from their symptoms ( recovery group) ( n = 11); Patients were scanned prior to therapy (T1), one week (T2) and five months after the end of therapy (T3). The second group included patients which followed a supportive therapy and remained symptomatic ( wait-list group) ( n = 7). They were scanned at three time-steps mimicking the same inter-scan intervals. Voxel-based morphometry (VBM) was used to characterize GM density evolution. GM density values showed a significant group-by-time interaction effect between T1 and T3 in prefrontal cortex areas. These interaction effects were driven by a GM density increase in the recovery group with respect to the wait-list group. Symptoms removal goes hand-in-hand with GM density enhancement of structures involved in emotional regulation. Highlights: This study explores the link between PTSD symptoms decrease and grey matter density increase in the prefrontal cortex. GM density enhancement in prefrontal areas suggests a potential reversibility of stress-induced effects. EMDR seems to be an efficient therapy to reduce PTSD symptoms and further restore brain structural organization.